Peer-driven quality improvement among health workers and traditional birth attendants in Sierra Leone: linkages between providers' organizational skills and relationships. Issue 1 (December 2015) - Higgins-Steele, Ariel; Waller, Kathryn; Fotso, Jean; Vesel, Linda
Abstract Background Sierra Leone has among the poorest maternal and child health indicators in the world and investments in public health have been predominately to increase demand for services, with fewer initiatives targeting supply side factors that influence health workers' work environment. This paper uses data from the Quality Circles project in a rural district of Sierra Leone to achieve three objectives. First, we examine the effect of the intervention on organizational skills and relationships among coworkers as well as between health workers and traditional birth attendants. Second, we examine whether changes in organizational skills are associated with changes in relationships among and between formal and informal health providers and between health providers and clients. Third, we aim to further understand these changes through the perspectives of health workers and traditional birth attendants. Methods The Quality Circles project was implemented in Kailahun District in the Eastern province of Sierra Leone from August 2011 to June 2013, with adjacent Tonkolili District serving as the control site. Using a mixed-methods approach, the evaluation included a quantitative survey, in-depth interviews and focus group discussions with health workers and traditional birth attendants. Mean values of the variables of interest were compared across sub-populations, and correlation analyses were performed between changes in organizational skills and changes in relationships. Results The results demonstrate that the Quality Circles intervention had positive effects on organizational skills and relationships. Furthermore, improvements in all organizational skill variables – problem-solving, strategizing and negotiation skills – were strongly associated with a change in the overall relationship variable. Conclusions The Quality Circles approach has the potential to support health workers to improve their organizational skills and relationships, which in turn can contribute to improving the interpersonal dimensions of the quality of care in low-resource contexts. This method brings together peers in a structured process for constructive group work and individual skill development, which are important in low-resource contexts where active participation and resourcefulness of health workers can also contribute to better health service delivery.